FACTORS ASSOCIATED WITH KNOWLEDGE, PERCEPTION, AND PRACTICE TOWARD SELF-CARE AMONG ELDERLY PATIENTS SUFFERING FROM TYPE 2 DIABETES MELLITUS IN RURAL THAILAND - Eknithiset, Rapat; Somrongthong, Ratana; Kumar, Ramesh (Journal of Ayub Medical College Abbottabad, 2017)
Background: Globally, diabetes caused 4.6 million deaths during 2011 and burdened health care systems worldwide with 465 billion. The diabetes prevalence rate in Thailand has risen dramatically in recent years, from just 2.3% in 1991 to 6.9% in 2009. The objective of this study was to explore factors associated with knowledge, perception, and practice toward self-care among elderly type 2 diabetes mellitus patients aged 50-70 years. Methods: A cross sectional study design was conducted by enrolling 140 aged people of both gender suffering from type 2 diabetes mellitus and registered at three clinics of Primary healthcare at Taladnoi, Horathep, and Khokyai, Saraburi, Thailand. Participants whose age was 50-70 were rechecked through laboratory testing like Hba1c, FBS, and BMI were included. Data was analysed by using descriptive statistics and chi-square. Results: The participants mean age was 62.11±0.59 years and 69.4% were female, 27.8% belonged to indigenous caste and 82.6% were married. About one-fourth of the participants were housewives, 15.2% government employee and 12.1% were farmer. Participants suffering from diabetes since1-5 years were 48.5%. Among the diabetic patients, 51.5% reported to have family history of diabetes. The mean knowledge score of the respondents was 3.61 (±1.80), perception was 4.34 (±1.41), practice was 12.14 (±4.47). A significant different existed between gender with Hba1c (<0.05), knowledge, and work status with Hba1c (<0.05). Conclusion: Study concluded that the knowledge, perception, and practice about type 2 diabetes mellitus among patient were significantly poor. However, the factors like; gender, work and practice were found significantly correlated with glycated haemoglobin. Keywords: Diabetes Mellitus Type 2; Knowledge; Perception; self-care; elderly population and associated factors